Evaluating the effectiveness of spatial augmented reality in smart manufacturing: a solution for manual working stations - Uva, Antonio E.; Gattullo, Michele; Manghisi, Vito M.; Spagnulo, Daniele; Cascella, Giuseppe L.; Fiorentino, Michele (International journal of advanced manufacturing technology, 2018)
Augmented reality (AR) is a key technology for the development of smart manufacturing. One of the main advantages of AR is that it can help workers to accomplish several tasks, making it possible the shift from mass production to mass customization. However, it is still not clear how these promises can be fulfilled in an industrial scenario. In particular, the question about which display solutions fit better the industrial constraints remains open. Based on the literature overview, laboratory experiments, and feedbacks from industrial companies, we supported the use of spatial augmented reality (SAR), designing a prototype intended to be used for manual working stations of the future smart factories. This work presents the evaluation of the effectiveness of conveying technical instructions with this SAR prototype as compared to paper manual. We run a within-subjects experiment with 16 participants to measure user task performance (completion times and error rates) and to collect subjective evaluation. We projected technical information on a motorbike engine during a seven-task maintenance procedure. Our results proved that SAR technology improves the operators’ performance with respect to a paper manual and that users well accept it. We found that SAR is more effective for difficult tasks than for simple ones and that the main advantage of SAR is related more to the reduction of error rates than to completion times. These results confirm the goodness of our design choices; then our prototype can be a valid candidate solution for a smart manufacturing application.